Chemotherapie-induzierte periphere Neuropathie - Gießen-Jung, Clemens; von Baumgarten, Louisa (DMW - Deutsche Medizinische Wochenschrift, 2018)
Chemotherapy-induced peripheral neuropathy (CIPN) is a severe and common side effect induced by a variety of anticancer drugs. CIPN presents as a sensory, motor, and sometimes autonomic dysfunction with a large variability, from a mild tingling sensation and hyperesthesia, to severe neuropathic pain. Up to 40 % of patients will develop CIPN which may lead to dose-reduction or discontinuation of their current treatment and largely affects their quality of life (QoL). This review presents specific clinical features and pathomechanisms and discusses current preventive strategies and therapeutic options.
Keywords: Chemotherapie-induzierte periphere Neuropathie (CIPN); Vincaalkaloide; Platinderivate, Prävention